BIOLOGICAL ASSET DISCLOSURE: A STUDY ON AGRICULTURAL COMPANIES IN INDONESIA - Owen, Michael; Radianto, Wirawan Endro Dwi (Jurnal Akuntansi Kontemporer, 2024)
Research Purposes. This research aims to investigate the effect of biological asset intensity and the characteristics of boards of directors on the disclosure of biological assets.Research Methods The population in this study is the agriculture companies listed on the BEI using a purposive sampling method with 216 samples between 2005 and 2021. Data analysis uses multiple linear regression using STATA version 17.Research Results and Findings. The result indicates that biological asset intensity, board of directors size, and board of directors accounting expertise positively affect the disclosure of biological assets. The evidence has direct implications for companies in selecting directors, as stakeholders may demand the appointment of directors with accounting experts.